LÁ¤ngle, Alfried (2008). Vivir con sentido. Lumen, Buenos Aires. Título original: Sinnvoll leben. Angewandte Existenzanalyse. By NP Buchverlag. Niederösterreichisches Pressehaus. St.Pölten.Viena.Linz. (Revista de Psicología, 2019)
.